NICKEL ORE EXPORT PROHIBITION IN THE FRAMEWORK WORLD TRADE ORGANIZATION AS AN EFFORT TO PROTECT NATURAL RESOURCES (WTO Case Study DS592: Indonesia Measures Relating to Raw Materials) - Cahya Putri Febiola; Charine Alya Pratiwi; Ratna Atiqah Salsabila; Adimas Bramantyo (Jurnal Ilmiah Advokasi, 2024)
Indonesia issued a policy prohibiting the export of nickel ore with a grade <1.7% in Minister of Energy and Mineral Resources Regulation Number 11/2019, but this policy gave rise to a lawsuit from the European Union at the WTO. The aim of this research is to find the implementation of the adoption of the WTO concept in the Indonesian legal system and answer dispute resolution between Indonesia and the European Union regarding the policy of banning Indonesian nickel ore exports as an effort to protect natural resources based on GATT/WTO rules and principles. This research uses a normative method using a case approach, statutory approach and conceptual approach. The research results show that the ban on nickel ore exports is Indonesia's effort to protect its natural resources, despite legal challenges from the European Union. The implementation of the GATT/WTO concept in Indonesian policy shows a balance between international obligations and national interests in managing natural resources. This dispute also highlights the importance of appropriate legal strategies in safeguarding state sovereignty within the WTO framework.